Catheter Ablation for Atrial Fibrillation in Patients With Watchman Left Atrial Appendage Occlusion Device: Results from a Multicenter Registry. (19th January 2017) - TURAGAM, MOHIT K.; LAVU, MADHAV; AFZAL, MUHAMMAD R.; VUDDANDA, VENKAT; JAZAYERI, MOHAMMAD‐ALI; PARIKH, VALAY; ATKINS, DONITA; BOMMANA, SUDHARANI; DI BIASE, LUIGI; HORTON, RODNEY; BAI, RONG; SWARUP, VIJAY; et al.
AF Ablation After Watchman: Background: There have been an increasing number of atrial fibrillation (AF) patients with Watchman left atrial appendage occlusion (LAAO) device, requiring catheter ablation (CA) for maintenance of normal sinus rhythm. In this study, we describe our experience with the feasibility and safety of CA in patients with a preexisting Watchman LAAO device. Methods: This was a retrospective multicenter AF registry of 60 patients with Watchman LAAO device who underwent CA for AF. Baseline clinical and procedural characteristics of the included subjects were retrieved from review of medical records and were analyzed. Results: The mean age was 72.7 ± 4.9 years and the mean CHADS2 score was 2.3 ± 0.6. All patients had successful pulmonary vein isolation (PVI). The left atrial appendage (LAA) was electrically active in 34 (56%) while reentrant tachycardia and AF triggers were seen in 17 (28%) patients. Electrical isolation was attempted in these 17 patients with only 10 achieving complete LAA isolation. Repeat imaging showed new peri‐device leaks in 30% (12/40) patients, while new significant peri‐device leaks (≥5 mm) were noted in 10% (10/40) of patients after RFA, respectively, requiring continuation of oral anticoagulation. There were a higher proportion of patients with severe peri‐device leaks (≥5 mm) after LAA isolation. However, >50% of those leaks sealed off on follow‐up transesophageal echocardiogram. Conclusion: AF ablation is a feasible and safe in patients with preexisting Watchman LAAO device. Electrical isolation of the LAA could be difficult and when attempted can result in increased risk of short‐term peri‐device leak and recurrence of AT/AF in almost all patients.